2016
DOI: 10.21894/jopr.2016.2804.13
|View full text |Cite
|
Sign up to set email alerts
|

POTENTIAL USES OF OIL PALM (Elaeis guineensis) LEAF EXTRACT IN TOPICAL APPLICATION

Abstract: The antioxidant, anti-microbial activity and potential application of oil palm (Elaeis guineensis) leaf extract (OPLE) as a skin lightening and sunscreen agent in topical application were evaluated. Currently, there are no evidence of skin lightening effect and protection against ultraviolet (UV) irradiation of OPLE. OPLE contains 9.84±0.06 mg gallic acid equivalent per gram of dry extract and shows antioxidant activity through 2,2-diphenyl-1-picrylhydrazyl assay with IC 50 of 247±0.58 µg ml -1 . OPLE was effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The OPLE was also reported to have antimicrobial activities, 11,39 tyrosinase inhibition for skin whitening purpose, and protection against UV radiation. 11 Thus, OPLE potentially can be used as active ingredient for topical application. The extract was also shown to have wound healing properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The OPLE was also reported to have antimicrobial activities, 11,39 tyrosinase inhibition for skin whitening purpose, and protection against UV radiation. 11 Thus, OPLE potentially can be used as active ingredient for topical application. The extract was also shown to have wound healing properties.…”
Section: Discussionmentioning
confidence: 99%
“…9,12 The OPLE comprises (À)-catechin gallate, ferulic acid, and phenolic acids, such as gallic acid and protocatechuic acid. 13,14 A recent study by Yusof et al 11 suggested that OPLE can potentially be used as a functional active ingredient for topical application where they demonstrated that OPLE has antimicrobial activity, antityrosinase activity, and protection against ultraviolet (UV) radiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…epigallocatechin (0.08%), catechin (0.30%), epicatechin (0.01%), epigallocatechin gallate (0.28%) and epicatechin gallate (0.05%) are among the reported phenolic compounds existing in OPLE [14]. There are claims of glycosylated flavonoids, ferulic acid, gallic acid, protocatechuic acid and carotenoids being present, too [15].…”
Section: ■ Introductionmentioning
confidence: 99%
“…Owing to their high fiber and nutrient composition, the OPLs are utilized as animal feed, in the production of pulp and paper, wood-based construction materials, fillers in polymer composites, and renewable sources for carbon and ethanol production. Despite these uses, the OPLs are still considered underutilized [7,8,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%